Health Care in Aged Population: A Global Public Health Challenge - Rahman, Md Shahidur (Journal of Medicine, 2019)
Health care and health care delivery systems will be burdened by growing number of ageing population and is going to be the next global public health challenge. Advances in medicine and socioeconomic development have substantially reduced mortality and morbidity. As a result number of aged is increasing with age related morbidity. These demographic and epidemiological changes, coupled with rapid urbanization, globalization, and accompanying changes in risk factors and lifestyles, have increased the prominence of chronic conditions. Health systems need to find effective strategies to extend health care and to respond to the needs of older adults. The goal of ensuring healthy lives and promoting wellbeing for everyone at all ages cannot be achieved without attention to the health of older adults. With an increasingly large proportion of this population living in low-income and middle-income countries, this will have implications worldwide. This literature based review intends to explore the spectrum of global challenge in geriatric health care. J MEDICINE JUL 2019; 20 (2) : 95-97